TELAAH TERHADAP PERKEMBANGAN TIPE TATANAN HUKUM DI INDONESIA PERSPEKTIF PEMIKIRAN NONET-SELZNICK MENUJU HUKUM YANG BERKEADILAN - Antasari, Rr Rina (Universitas Islam Negeri Raden Fatah Palembang, 2019)
The Idea of ​​the needs for legal review of the type of Indonesian state law in order to be able to answer legal problems in the community with a sense of justice from the perspective of Nonet and Selznick's thinking. Contradictory issues at the level of legal concepts in the perspective of the development of life in Indonesian society continue to roll, some problems are found, including: 1) the implementation of law as an order system in Indonesia contradicts the implementation of the law as a disorder system; 2). The analysis between the enactment of law and social change is contradictory to the theoretical review of the development of legal orientation as a tool for social change; 3). The concept of law enforcement and social change in achieving development is contradictory to the concept of implementing legal functions as a social controller in law enforcement; and 4) Between state equipment and law enforcement in the mechanism of the criminal law system, for example, contradictions occur with the urgency of the position of advocates as a means of law enforcement in the mechanism of the criminal law system. So that the problem in this study is the development of types of legal order in Indonesia from the time of independence until now in the perspective of Nonet and Selznick's thinking and type of legal order from the perspective of Nonet Selznick's thinking that is appropriate to be applied in Indonesia that can provide a sense of justice the ideals of the Indonesian law.